Subjective Cognitive Complaints in the Working Population : The Influence of Objective Cognitive Functioning and Working Conditions - Stenfors, Cecilia U. D. (Stockholms universitet, Psykologiska institutionen, 2013)
Cognitive functioning is important for managing work and life in general. However, subjective cognitive complaints (SCC), involving self-perceived difficulties with concentration, memory, decision making, and clear thinking are common in the general and in the working population and can be coupled with both lowered well-being and work ability. The present thesis investigated the extent to which SCC among people in the work force can be explained by objective cognitive functioning (study I & II) and working conditions (study III), utilizing samples from the working population. The potential roles of other common psychological problems which often co-occur with SCC were also investigated in studies I-III. In Study I, high levels of SCC were associated with significantly poorer episodic memory performance during high executive demands and a trend was found towards poorer episodic memory, while not being associated with semantic memory. In Study II, high levels of SCC were associated with significantly poorer executive cognitive performance on all three executive cognitive tests used. Symptoms of depression, chronic stress and sleeping problems were found to play an important role in the relations between SCC and episodic memory during divided attention in study I and executive cognitive functioning in study II. In Study III, in all cross-sectional data analyses, high quantitative demands, information and communication technology (ICT) demands, underqualification in the work situation and inter-personal conflicts were positively associated with SCC, whereas social support, good resources at work and overqualification in the work situation were negatively associated with SCC. In all prospective data analyses, quantitative job demands, ICT demands and underqualification were positively associated with future SCC, including when adjusted for baseline cognitive complaints. The findings may guide prevention of and interventions for SCC among people in the work force. === At the time of the doctoral defense, the following papers were unpublished and had a status as follows: Paper 1: Submitted. Paper 2: Accepted.